Implementation and early outcomes for a surgeon‐directed hepatic arterial infusion pump program for colorectal liver metastases. Issue 7 (30th October 2018) - Chakedis, Jeffery; Beal, Eliza W.; Sun, Steven; Galo, Jason; Chafitz, Aaron; Davidson, Gail; Reardon, Joshua; Dillhoff, Mary; Pawlik, Timothy M.; Abdel‐Misih, Sherif; Bloomston, Mark; Schmidt, Carl R.
Abstract : Introduction: Hepatic arterial infusion pump (HAIP) therapy for colorectal liver metastases (CRLM) is beneficial in selected patients yet wide acceptance in the oncology community is lacking. Methods: A surgeon‐led team implemented a HAIP program in 2012. Pumps were placed by laparotomy for CRLM and fluorodeoxyuridine was infused via HAIP every 28 days without systemic chemotherapy supervised by the operating surgeon. Results: Sixty patients were treated with HAIP, either in the adjuvant setting after liver resection or ablation of CRLM in 26 (43%) patients or with the unresectable disease in 34 (57%). Perioperative complications occurred in 19 (32%) and pump‐specific complications in 14 (23%) that included intrahepatic biliary stricture in one (2%). Time to liver progression was a median 9.2 months (95% CI, 3.1‐15.3 months) in unresectable patients and liver recurrence was a median 24.7 months (2.5‐46.9 months) in the adjuvant group. Estimated 3‐year overall survival from the time of HAIP placement was 64% in the adjuvant group and 37% in the unresectable group. Sarcopenia was prevalent (48%) and was associated with a worse survival (HR 2.4, 95% CI, 1.1‐5.0). Conclusion: A surgeon‐led HAIP program may achieve outcomes on par with those of experienced centers and foster strong relationships between surgical and medical oncologists.